Global trends and hotspots on childhood obstructive sleep apnea: a 10-year bibliometric analysis - Chao Wang; Chao Wang; Kai Sun; Siyao Zhang; Huiying Hu; Yuanyuan Lu; Kai Liu; Zhenkun Yu; Zhenkun Yu (Frontiers Media S.A., 2023)
BackgroundObstructive sleep apnea (OSA) is children's most common sleep-related breathing disorder. It may develop a wide range of severe complications if not diagnosed promptly and treated effectively. However, Childhood OSA has not specifically been analyzed using a bibliometric approach.MethodsWe respectively collected the research results of childhood OSA from 2013 to 2022 through Web of Science and PubMed. Vosviewer, CiteSpace, and bibliometric online analysis platforms were used for visualizing and analyzing the literature. The MeSH terms were bi-clustered using the Bibliographic Item co-occurrence Matrix Builder (BICOMB) and graph clustering toolkit (gCLUTO) to identify the hotspots.Results4022 publications were finally identified on childhood OSA from 2013 to 2022. The United States has the largest number of publications (1902), accounting for 47.29%. University of Cincinnati is the most productive organization (196), followed by the University of Pennsylvania (151). The most prolific journal was the International Journal of Pediatric Otorhinolaryngology, with 311 documents published. In comparison, Pediatrics is the most cited journal (6936). Gozal D ranked highest among all authors in publication (192). Burst detection shows continuous positive airway pressure, Robin sequence, and nocturnal oximetry are recent keywords of great interest to researchers. Five hotspots were identified by co-word biclustering.ConclusionResearch over the past ten years has been fruitful, establishing the foundation for childhood OSA. Clusters (0-4) of high-frequency Major Mesh topics have attracted extensive attention. Evaluation and treatment methods of childhood OSA remain major focuses. We believe this article will provide other researchers with new directions and may contribute to a future breakthrough in this field.